A Case of Electrical Burns Injury with A History of Heart Disease: A Case Report - Rahman, Lutfi; Yuliandani, Erin; Masruroh, Rurin; Mirwanti, Ristina; Priambodo, Ayu Prawesti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Burns are serious injuries that can have significant physical and psychological impacts on individuals. Burns due to electric shock are relatively rare but carry a high risk of serious complications, including respiratory problems and fluid loss that can be life-threatening. Purpose: The purpose of this study is to present the case study of burn electrical burns injury with a history of heart disease. Methods: This study used a case report approach on one patient. Data were collected by conducting interviews and assessments to one patient with electrical burn injury with a history of heart disease. Data analysis was carried out by comparing the results of the assessment with the theory of electrical burn injury. Results: The results of this study indicate that Mr. P, aged 35 years, showed burns covering 65% of the total body surface, with grade III severity. The patient also experienced respiratory problems with SpO2 85%. In addition, other nursing diagnoses were found such as impaired airway clearance due to edema in the larynx, hypovolemia due to active fluid loss, and acute pain due to physical injurious agents. This is the importance of proper and rapid assessment to reduce the risk of more serious complications. Conclusions: Holistic therapy and a multidisciplinary approach are key in providing optimal care and minimizing the risk of complications in patients with complex conditions such as this.